Synthesis and crystal structure of 1-((3R,10S,13R,17S)-3-((4-methoxyphenyl)amino)-10,13-dimethylhexadecahydro-1H-cyclopenta[α]-phenanthren-17-yl)ethan-1-one, C28H41NO2 - Zhang Wen-Wen; Ye Jiang-Hai; Huang Hua; Zou Juan; He Kang (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C28H41NO2, orthorhombic, P212121 (no. 19), a = 10.4480(5) Å, b = 12.4188(6) Å, c = 18.3905(10) Å, V = 2386.2(2) Å3, Z = 4, Rgt(F) = 0.0608, wRref (F2) = 0.1510, T = 273(2) K.